PO262 Endovascular stroke treatment, a new era – cheshire & merseyside regional experience. (1st December 2017) - Boztepe, Selda; Sekhar, Alakendu; Menon, Ranjith; Puthuran, Mani; Nasher, Hans; Chandran, Arun; Bhojak, Manish; Wilson, Martin; Nicholson, Andrew
Abstract : The stroke treatment world wide has seen a giant leap in last few years as the science has moved from systemic infusion of clot busting drugs to highly selective intra arterial intervention. The intervention requires careful selection of subset of stroke secondary to large vessel occlusion in a timely fasshion. Since the publication of MR CLEAN ( Multicenter Randomised CLinical trial of Endovascular treatment for acute ischaemic stroke in the Netherlands) trial in 2014 and recent NICE approval to provide this service UK wide stroke services will face challanges to provide this in an equitable fashion. We at Walton Centre have been providing this service to the whole of Cheshire, Merseyside since 2013. Through this audit we would like to share our experience of stroke intervention in this stand alone neurosciences centre. This audit compared the standards against the European Stroke organisation guidelines for ischaemic stroke 2016. We measured the following key parameters along with clinical outcome. 1) Does recanalisation influence immediate neurological recovery. 2) Does bridging thrombectomy (IV thrombolysis +thrombectomy) differ from primary thrombectomy. 3) Does performing the service out of hours influence the outcome